The phenomenon of code-mixing in media information in public space - Hidayanti, Ni Nyoman Ayu Tri; Sucipta, I Made Darma; Widanta, I Made Rai Jaya (Institute of Computer Science (IOCS), 2025)
Cross-language communication, which cannot be avoided in the use of language in this digital era, is the main focus in language. One form of language use that often occurs today is code mixing. Code mixing is the mixing of two (or more) languages or varieties of languages in a language act. In Indonesia, there is a lot of use of the Indonesian language, especially in information media such as advertisements, banners, billboards, information signs which are often found in public spaces. This research discusses the use of code-mixed language in information media in public spaces such as advertisements, banners, billboards and information signs. The method used in this research is descriptive analysis which is used by collecting appropriate data and then analyzing it to find out the existing problems. The data collection technique used is documentation, notes, then analysis from several sources. The results obtained show that the Indonesian language used in several information media in the public space is very varied. There were several uses of inward and outward code mixing, of which inward code mixing was found 2 data using Indonesian and Balinese, while outward code mixing was found 8 data using Indonesian and English. The use of code mixing in advertising language here is as an attraction so that readers can more easily understand an advertisement in their memory.